Transformasi Sosial Hukum Hak Asasi Manusia Internasional Melalui Mahkamah Konstitusi Indonesia - Mirza, Isroni Muhammad Miraj; Natamiharja, Rudi; Serna, Jalil Alejandro Magaldi (Faculty of Law, Universitas Jambi, 2023)
The importance of human rights in international law cannot be overstated. International Law plays a fundamental role in safeguarding and promoting human rights, which are safeguarded through a variety of legal instruments, including international conventions and international declarations, both of which are recognized as instruments of international law. The fundamental principles of Human Rights are recognized in the legal system of Indonesia. These fundamental principles are expressed in the Constitution and its related legal documents through the provisions and values that govern human rights. Thus, the preamble of the Constitution of the Republic of Indonesia includes the fundamental principles of Self-determination, Independence, Security, Social Welfare, and Education. This research will look at how the Indonesian Constitution regulates and guarantees the implementation of international human rights law through the Indonesian Constitutional Court, as well as how these rights are integrated into society from both the government's and society's perspective. This research is done through interdisciplinary approach, combining legal, social, and comparative studies. Ultimately, it's about how Indonesia's Consitutional Court can help make human rights practices better and more effective. As the highest judicial organ of a state, it is essential for the Constitutional Court to effectively and effectively implement the international human rights system as we know it in order to safeguard the interests of all stakeholders, especially in Indonesia. Keywords: human right ; constitution; International law;